Toward Making Poly(ethylene terephthalate) Degradable in Aqueous Environment. Issue 4 (2nd January 2022) - Li, Yanyan; Chen, Junhe; Han, Wanli; Yi, Hongling; Wang, Jianning; Xing, Peixiang; Ren, Jiaxiang; Yao, Donggang
Abstract: Polyethylene terephthalate (PET) is a non‐biodegradable polymer, and it takes hundreds of years or longer to degrade in nature. In the current study, it is demonstrated that the addition of calcium oxide (CaO) into PET renders a degradable PET in an aqueous environment. Specifically, PET/CaO composite samples are prepared by melt mixing and compression molding, and the capability of hydrolysis of the composite in an aqueous environment is evaluated using different characterization and testing methods. The results show that the PET/CaO mixture is thermally stable during melt processing, and the resulting composite undergoes controllable hydrolysis in a water bath with calcium terephthalate as a main hydrolysis byproduct. The PET/CaO composite is mechanically strong; for example, a 75/25 PET/CaO sample shows a strength comparable to that of the pure PET polymer. The results further show that the hydrolysis of the PET/CaO composite may be promoted by addition of other fillers such as glass fibers. It is anticipated that the development of such a degradable PET material may impact a number of application areas where disposable packaging materials and water dissolvable composite products are desired. Abstract : A degradable PET composite is produced by melt mixing and compression molding PET with CaO. The obtained PET/CaO composite is mechanically strong and exhibits comparable strength with pure PET, yet it undergoes controllable hydrolysis in a water bath with CaTP as the main by product. A framework for processing PET wastes into water dissolvable value‐added composites is also discussed.